Localization of the spectral expansions associated with the partial differential operators - Rakhimov, Abdumalik A. (Cankaya University Press, 2017)
In this paper we prove precise conditions of the summability and eqiu-summability of the spectral expansions associated with partial differential operators. It is established sharp relations between index of summation and singularity of the distribution.